The impact of social norms and conformity on cyberbullying perpetration among adolescents: an integration of the theory of planned behavior model - Prestera, Giulia; Amadori, Alberto; Sangiuliano Intra, Francesca; Taverna, Livia; Basso, Demis; Brighi, Antonella (Frontiers in Psychology, 2025)
IntroductionIn recent years, literature has focused on the social factors that influence cyberbullying behavior among adolescents. According to the most recent perspective on cyberbullying, online aggression includes both direct interactions and the broader social environment, highlighting the critical role of social norms in influencing such behavior. This study examines how social norms and conformism influence adolescents' cyberbullying perpetration, addressing the gap in understanding how social pressure and interpersonal factors impact these actions within the Theory of Planned Behavior.MethodA total of 1,081 adolescents participated to our study. Structural equation modeling was used to test the effect of social norms and conformism on the Theory of Planned Behavior construct applied to cyberbullying.ResultsResults indicated a positive association between social norms, situational self-efficacy, and cyberbullying perpetration. Additionally, conformism was positively associated with both subjective norms and situational self-efficacy. Attitude, subjective norms and situational self-efficacy were all positively linked to the intention to engage in cyberbullying, with intention showing a direct positive association with cyberbullying.DiscussionThe present study integrated the application of Theory of Planned Behavior model to cyberbullying perpetration, providing evidence for the significant role of social norms and conformism. The results of this research are instrumental in developing targeted prevention and intervention strategies which recognize the role of peer groups dynamics and adherence to social norms, thereby improving efforts to prevent and address cyberbullying among youth.